CENTRALIZED ELECTRICAL BUILDING SYSTEM - Cornell, Grant B. (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on the design and development of the Centralized Electrical Building System, and the phases of its construction. The foremost objective is to make sure that the performance of the developed system is satisfactory concerning its functionality, effectiveness, usefulness, and acceptability. It documents the works done by the researchers. The researchers work on switching electrical devices inside the building through a computer unit. The program starts automatically in the computer start-up process. Clicking the buttons of the user interface initiates the switching process of the system. Furthermore, the system shows update and verification for each command. The system consists of a controller (computer program), hardware interface and access outlets for electrical loads. The system is integrated with switching components that will allow the flowing of current on electrical loads to be controlled remotely. Monitoring of the conditions of the loads is included to immediately respond to needs such as lighting perimeter lamps and the likes. The timing circuit is also integrated into the program to automatically turns on and shuts off lights as necessary. It was found out that first prototype is functioning well except for the electromechanical relays which were easily damaged during the testing because of the electrical spark it produces each time they are actuated. The electromechanical relays were replaced by optoisolators and solid state relays for better efficiency. Subjecting the prototype to assessment by selected users and experts yielded positive responses as they perceived that the prototype is very functional, efficient, useful, and acceptable.